The GBPUSD Exchange Rate Over the Last 50 Years - Michail, Nektarios A. (My University, 2025)
This paper examines the reasons behind the long-run depreciation of the Sterling against the US Dollar. Using data that range from January 1971 to July 2023 and a Vector Error Correction model, the results show that higher UK inflation in the 1970s and early 1980s, as well as the relative overperformance of US markets since 2010 are the main reasons behind the depreciation from 2.41 to 1.29 over the course of 54 years. Other than these two factors, interest rates also appear to have played a role, especially in the 1970s–80s, since the relatively higher bond yields in the UK appear to have prevented the exchange rate from further depreciating. When extending the model to include economic policy uncertainty and geopolitical risk, the above results remain the same, with policy uncertainty having a negative impact on the exchange rate since 2015.